Child-focused state cash transfers and adolescent risk of HIV infection in South Africa: a propensity-score-matched case-control study - Lucie Cluver, PhD; Mark Boyes, PhD; Mark Orkin, PhD; Marija Pantelic, MSc; Thembela Molwena; Lorraine Sherr, PhD (Elsevier, 2013)
Background: Effective and scalable HIV prevention for adolescents in sub-Saharan Africa is needed. Cash transfers can reduce HIV incidence through reducing risk behaviours. However, questions remain about their effectiveness within national poverty-alleviation programmes, and their effects on different behaviours in boys and girls. Methods: In this case-control study, we interviewed South African adolescents (aged 10-18 years) between 2009 and 2012. We randomly selected census areas in two urban and two rural districts in two provinces in South Africa, including all homes with a resident adolescent. We assessed household receipt of state-provided child-focused cash transfers, incidence in the past year and prevalence of transactional sex, age-disparate sex, unprotected sex, multiple partners, and sex while drunk or after taking drugs. We used logistic regression after propensity score matching to assess the effect of cash transfers on these risky sexual behaviours. Findings: We interviewed 3515 participants (one per household) at baseline, and interviewed 3401 at follow-up. For adolescent girls (n=1926), receipt of a cash transfer was associated with reduced incidence of transactional sex (odds ratio [OR] 0·49, 95% CI 0·26-0·93; p=0·028), and age-disparate sex (OR 0·29, 95% CI 0·13-0·67; p=0·004), with similar associations for prevalence (for transactional sex, OR 0·47, 95% CI 0·26-0·86; p=0·015; for age-disparate sex, OR 0·37, 95% CI 0·18-0·77; p=0·003). No significant effects were shown for other risk behaviours. For boys (n=1475), no consistent effects were shown for any of the behaviours. Interpretation: National, child-focused cash transfers to alleviate poverty for households in sub-Saharan Africa can substantially reduce unsafe partner selection by adolescent girls. Child-focused cash transfers are of potential importance for effective combination strategies for prevention of HIV. Funding: UK Economic and Social Research Council, South African National Research Foundation, Health Economics and AIDS Research Division at University of KwaZulu-Natal, South African National Department of Social Development, Claude Leon Foundation, John Fell Fund, Nuffield Foundation, and Regional Interagency Task Team for Children affected by AIDS-Eastern and Southern Africa.